Due codici bobbiesi gemelli, un restauro quattrocentesco: il manoscritto F.IV.8 della Vita Gregorii Magni di Giovanni Immonide nella Biblioteca nazionale universitaria di Torino - Rosso, Chiara (Scrineum, 2023)
The paper focuses on the late ninth-century Bobbio manuscript Torino, Biblioteca nazionale universitaria, F.IV.8, witness of Iohannes Hymmonides’ Vita Gregorii Magni, followed by the slightly later-added text of the visio Dryhthelmi, from Bede’s Historia ecclesiastica (V, 12). The codex bears clear traces of a mid-fifteenth-century restoration, aimed at filling lacunae of various entities along the text. The presence of two conspicuous errors, respectively between quires 12 and 13, and quire 16 and f. 124, urges further codicological and paleographical investigation on the codex. From this analysis some clues emerge to the existence of two ʻtwinʼ codices, which were merged together, in order to make one manuscript out of two formerly autonomous, damaged witnesses. Eight fragments once belonging to these two copies of the Vita Gregorii and then reused as guard-leaves in other Bobbio manuscripts now preserved in the Ambrosiana and Vaticana Libraries, as well as in the Turin Library itself, corroborate the hypothesis. It thus appears that, shortly after the publication of the biography of Gregory the Great, the Bobbio scriptorium drawn it up in two copies, the one for the abbey library, the other for the nearby small book collection kept at the Spelunca.